Sifat-Sifat Time-Series dari Angka Akuntansi dan Konservatisme Industri Manufaktur - Nur Sayidah (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2005)
This research examines the changing time-series properties of accounting numbers and conservatism over 1995-2003. Accounting numbers which is studied are profitability, cash flow and accrual. We use accumulation of non operating accrual and variability of earning distribution as measures of conservatism. The result of every year analysis show that percentage of reporting losses and profitability have not specific pattern over research periods. The sub period analysis result the different finding. Percentage of reporting losses have increased from before monetary crisis to after monetary crisis. Profitability have decreased from before monetary crisis to after monetary crisis. Profitability fluctuation is not a result of change in the distribution of cash flow. T-test of non operating accrual accumulation and variability of earning distribution have evidenced an increasing of reporting conservatism.Keywords: conservatism, earning, cash flow, accrual